Phytochemical Analysis and Anti-Collagenase Activity of Celery (Apium graveolens L.) Extract - Fahrizal Amanda Permana; Meitha Khansa Khairunnisa; Purwanto Purwanto; Sri Handayani; Riris Istighfari Jenie (Majalah Obat Tradisional, 2025)
Aging is a normal process experienced by humans. One of the causes of aging is the body's intrinsic activity, such as the activity of one of the extracellular matrix-breaking enzymes, collagenase. Demand for skin care to prevent aging is increasing, especially plant-based skin care. This study aims to explore the potency of celery extract as an anti-collagenase. In this study, we used celery extract as a sample obtained from the maceration process by seventy percent ethanol 70% as the solvent. Sample compounds are then detected by LC-HRMS to determine the major compounds contained in a sample and their concentrations. Anti-collagenase activity was observed by enzymatic assay. The LC-HRMS analysis confirmed that apigenin, hispidulin, and catechin were included in the celery extract, with apigenin as the major compound of celery with AUC 73479.21×103, the AUC of hispidulin is 17063.21×103, and catechin 61.14×103. The percentage of collagenase inhibition of celery extract up until 200 μg/mL was 59.22% with an IC50 value of 132.48 µg/mL. These data indicated that celery containing apigenin, hispidulin, and catechin has an anti-collagenase activity worth further exploring for a healthy skin supplement.